The role of after-ripening in promoting germination of arid zone seeds: A study on six Australian species - Commander, L.; Merritt, D.; Rokich, D.; Dixon, Kingsley (2009)
The effects of after-ripening (storage under warm, dry conditions) on seed germination was examined in six plant species from the arid zone of Western Australia with the aim of improving germination and germination rate for rehabilitation objectives. Study species (Acanthocarpus preissii, Anthocercis littorea, Dioscorea hastifolia, Eremophila oldfieldii, Thryptomene baeckeacea and Zygophyllum fruticulosum) were selected based on diverse plant habits, seed types and requirements for rehabilitation. After-ripening was investigated by adjusting seed moisture content to 13 and 50 equilibrium relative humidity (eRH) at 23 °C and storing seeds at two temperatures (30 and 45 °C) from 1 to 18 months. Following storage, seeds were incubated in water, gibberellic acid (GA3) or karrikinolide (KAR1; the butenolide, 3-methyl-2H-furo[2,3-c]pyran-2-one). All after-ripening conditions increased germination percentage and rate of A. littorea and D. hastifolia, with A. littorea only germinating when treated with GA3 or KAR1. The germination of Z. fruticulosum was dependent on after-ripening temperature and seed moisture content. After-ripening had a limited effect on the remaining three species. The restoration implications of the findings are discussed. © 2009 The Linnean Society of London.